Preparing and Training for the Full Spectrum of Military Challenges Insights from the Experiences of China, France, the United Kingdom, India, and Israel - Johnson, David E. (RAND Corporation, 2009)
What can the United States learn from other militaries about how better to prepare for full-spectrum operations and deployments? The authors examine the militaries of China, France, the UK, India, and Israel to (1) identify different approaches to readiness, adaptability, and operational issues and (2) assess the ways in which units are trained both for specific and general deployments and for train, advise, and assist missions.